Exploration of Imam Al-Ghazali’s Islamic Economic Thought: A Systematic Literature Review - Febriza, Milla; Rozalinda, Rozalinda; Meirison, Meirison (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2025)
This study explores and synthesises the economic thought of Imam Al-Ghazali through a Systematic Literature Review (SLR) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) model. A qualitative SLR design was employed, drawing on articles published between 2015 and 2025, collected using the Publish or Perish software. The PRISMA framework guided the data screening and analysis, which is illustrated in a flow diagram. Out of 135 documents initially identified, 30 articles met the eligibility criteria and were included in the review. The results indicate that Al-Ghazali's economic thought is centred on several key themes: justice in economic activities, the intrinsic value of money, ethical consumption and production, and the importance of fair market mechanisms. In addition, Al-Ghazali emphasised the balance between the material and spiritual aspects of economic life and highlighted the state's role in promoting welfare and social justice. These ideas demonstrate enduring relevance for contemporary economic challenges, particularly in encouraging ethical practices and benefit-oriented systems. The findings are expected to provide a conceptual foundation for the development of Islamic economics rooted in moral and spiritual values.